2015
DOI: 10.3390/ijerph120505528
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity Levels and Sedentary Behaviors of Latino Children in London (Ontario, Canada)

Abstract: Objective: To assess the physical activity and sedentary behaviors of a sample of Latino children in London, Ontario, Canada. Methods: Seventy-four Latino children (54.1% male; mean age = 11.4) completed self-report questionnaires related to physical activity and sedentary behaviors. A subset of children (n = 64) wore Actical (Mini Mitter, Respironics) accelerometers for a maximum of four days. Results: Latino children self-reported moderate levels of physical activity (i.e., mean score of 2.8 on 5-point scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In fact, Diouf et al [26], in Senegalese school children aged between 8 and 11 years, reported a PAQ-C score of 2.42 ± 0.85 which is sex-dependent; girls were more engaged in light activity than boys. A Canadian study showed a mean activity score PAQ-C of 2.8 ± 0.6; boys self-reported as significantly more active than girls [27].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Diouf et al [26], in Senegalese school children aged between 8 and 11 years, reported a PAQ-C score of 2.42 ± 0.85 which is sex-dependent; girls were more engaged in light activity than boys. A Canadian study showed a mean activity score PAQ-C of 2.8 ± 0.6; boys self-reported as significantly more active than girls [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary lifestyle was more common among participants in higher grades, females and racial and ethnic minorities. 10,13 This study showed that obese children were 2.86 times more likely to be associated with television viewing time and is statistically significant (p=0.005). Similarly, obese children were also showed statistical significance with physical activity level (p=0.04) and LTPA level (p=0.00).…”
Section: Resultsmentioning
confidence: 66%
“…Another study showed that boys spend more time in screen related sedentary behavior than girls although the difference was not statistically significant (p=0.8). 10 Children of less educated mothers were watching an additional 2 hours of TV per day. 11 Though engaged in any of the occupation, this study showed no statistical association between mothers occupation type and children television viewing time (p=0.508).…”
Section: Resultsmentioning
confidence: 99%
“…Physical Activity Questionnaire. Participants completed the 6-item short version of the Physical Activity Questionnaire for Children (PAQ-C), which was previously validated and shown to be reliable and used with Latino children (Mandich, Burke, Gaston, & Tucker, 2015). The first question asked for a list of 23 activities: "Have you done any of the following activities [in your spare time] in the past 7 days (past week)?…”
Section: Methodsmentioning
confidence: 99%